2008
DOI: 10.2337/dc08-2034
|View full text |Cite
|
Sign up to set email alerts
|

Improving Diabetes Care in Practice

Abstract: OBJECTIVE -The purpose of this study was to determine whether implementation of a multicomponent organizational intervention can produce significant change in diabetes care and outcomes in community primary care practices.RESEARCH DESIGN AND METHODS -This was a group-randomized, controlled clinical trial evaluating the practical effectiveness of a multicomponent intervention (TRANSLATE) in 24 practices. The intervention included implementation of an electronic diabetes registry, visit reminders, and patient-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
141
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(146 citation statements)
references
References 22 publications
4
141
1
Order By: Relevance
“…These negative findings highlight the importance of delivering decision support information that is both timely and actionable. Another study in 24 practices in Minnesota, which included a case manager function, showed improvements in both process and outcome 15 . Other interventions have resulted in improvement in process but not laboratory outcomes 8,10,16 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These negative findings highlight the importance of delivering decision support information that is both timely and actionable. Another study in 24 practices in Minnesota, which included a case manager function, showed improvements in both process and outcome 15 . Other interventions have resulted in improvement in process but not laboratory outcomes 8,10,16 .…”
Section: Discussionmentioning
confidence: 99%
“…Interventions that add personnel 15,45,46 . Our study findings support the idea that practices interested in population-based chronic disease management may consider a laboratory-based registry and decision support system as a transition to a more fully integrated future including a broader team and improved electronic systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Each practice was rated twice by their assigned PF for each of these 9 elementsonce after the initial visit and once at the conclusion of project activities. Each TRANSLATE category was rated on a scale of 1 to 4, with 1 signifying no accomplishment and 4 signifying the highest accomplishment.…”
Section: Practice Readiness For Transformationmentioning
confidence: 99%
“…Single studies of interventions aimed at both patients and providers have yielded mixed results with respect to improving BP control in patients with diabetes. [29][30][31][32][33][34] However, systematic reviews and meta-analyses have demonstrated decreases in BP associated with group-based or individual patient education and team-based care involving nurses and pharmacists. [35][36][37] Hypertension: Initial Evaluation Patients with diabetes should have their BP measured and recorded at each office visit with an instrument that has been recently calibrated.…”
Section: Effectiveness Of Bp Control: Real-world Practicementioning
confidence: 99%